THE ROLE OF ONLINE LEARNING PLATFORMS IN TEACHING ENGLISH LANGUAGE - O‘lmasova Nodira (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: his article explores the role of online learning platforms in improving English language learning, with a particular focus on their impact on developing learners’ speaking skills. In the era of digital transformation, platforms such as Duolingo, Rosetta Stone, Babbel, and MOOCs (Coursera, EdX, FutureLearn) have become essential tools in modern education. The study analyzes how these platforms support language acquisition through gamification, immersive learning environments, interactive tasks, and artificial intelligence-based personalization.